Sharing economy: exploring social media and bibliometric evidence - Tomás, Bruno Miguel Pereira (2019)
The current structural changes in the world economy have led to the emergence and rapid proliferation of a new economic model whose individuals share assets owned by others. Thus was born the concept of Sharing Economy. This concept has been applied in several sectors with success as it is the case of the transport sector and the real estate sector. However, the Sharing Economy has become a complex phenomenon with several ramifications in different aspects, two of these same slopes are: academic and social. This thesis will focus on a big-time analysis of both strands. On the academic side, supporting a bibliometrics analysis will try to understand what the repercussions of this phenomenon at the level of academic publications, analyzing number of articles per year, authors, publications, terms and key articles. On the social side, relieving Crimson Hexagon's ForSight analysis software will analyze, number of tweets per year, authors and important events on the social network Twitter. This analysis has three main aims: firstly, to understand the phenomenon of Economy Sharing in the two aspects studied, secondly, to perceive the differences existing in the in the two strands studied and finally, using altmetrics discovering what is the difference between social relevant articles and the academic relevant articles of Sharing Economy.